Simulation and analysis of film bulk acoustic wave resonator for gas sensor - Nurul Izza Mohd Nor; Muhammad Rosmaidie Roslan; Nazuhusna Khalid; Hasnizah Aris; Muhammad Mahyiddin Ramli; Mohd Syafiq Mispan, (International Journal of Nanoelectronics and Materials (IJNeaM), 2025)
Developing gas sensors using Film Bulk Acoustic Resonators (FBARs) presents a multifaceted challenge centred around the identification of optimal piezoelectric and electrode materials. The resonance frequency, a critical parameter, must be precisely controlled to ensure efficient vibration, especially in the presence of specific gases that may alter this frequency. Balancing the quality (Q) factor is essential, as a higher Q factor contributes to sharper resonances, enhancing sensitivity. Hence, this work presents the analysis of various design parameters, piezoelectric materials, and electrode materials in enhancing the Q factor, thus improving the performance of FBAR for gas sensors. Comprehensive one-dimensional (1-D) modelling is utilized to optimize the device performance, focusing on variation of parameters such as thickness, width, and length of each layer of FBAR, piezoelectric materials, aluminium nitride (AlN), zinc oxide (ZnO), and electrode material, aluminium (Al). The optimized FBAR using AlN as the piezoelectric material shows better characteristics compared to FBAR using ZnO. The highest Q factor achieved was 8569 at 1 GHz with the area of 30 µm × 30 µm.